P121 Urban fine and coarse mode particulate matter differentially alter the maturation of monocyte-derived dendritic cells. (15th November 2016) - Ho, TR; Camina, N; Pfeffer, PE; Mann, EH; Mudway, IS; Hawrylowicz, CM
Abstract : Background: There is considerable evidence linking increased exposure to particulate matter (PM2.5 and PM10) to adverse respiratory outcomes, with patients with asthma and chronic obstructive pulmonary diseases (COPD) prone to more exacerbations and respiratory tract infections during pollution episodes. We have previously shown that peripheral human CD1c+ myeloid DCs, a key orchestrator of the adaptive immune response, promoted naive CD4+ T lymphocyte proliferation and increased expansion of potent inflammatory Th1 and Th17 effector cells when challenged with standard reference urban PM (SRM-1648a). However, monocyte-derived dendritic cells (MDDCs), which represent an inflammatory subset of DCs, may play a substantial role in lung inflammation. In this study, we investigated the effects of PM on MDDC maturation, focusing on responses to PM samples collected from the contemporary London airshed. Methods: PM2.5 and PM10 from a high traffic roadside site in London were collected (2/1/2013 – 15/1/2014) and pooled to generate representative annual samples. SRM-1648a and SRM-2975 (diesel exhaust derived PM) were used as control samples. Differentiated MDDCs, derived from CD14+ monocytes incubated with IL-4 and GM-CSF for 6 days, were challenged with these PM samples, plus control PM samples at various concentrations (2.5–20 µg/ml) for 24 hours. DC expression of CD83, MHC-I and MHC-II were measured by flow-cytometry. Results: Roadside PM10 and SRM-1648a exposure significantly increased the expression of MHC-II on MDDCs, whilst Roadside PM2.5 and SRM-2975 had no impact. There was also an increased expression of maturation marker CD83 when cells were exposed to Roadside PM10 and SRM-1648a, as well as Roadside PM2.5 at a higher concentration. However, exposure to all PM samples except for Roadside PM10 led to a significant decrease in MHC-I expression. Conclusion: PM fractions containing coarse mode material (SRM-1648a and PM10) appeared more able to stimulate MDDC maturation than fine mode PM (SRM-2975 and PM2.5). There was a clear decrease in MHC-I expression after exposure to most PM samples. This may indicate that MDDCs DCs exposed to PM are less able to stimulate CD8+ T cells, resulting in recurring respiratory tract infections. Understanding the immunological effects of different particle types will help guide public health interventions.